Automatic motorcycle signal indicator using arduino uno and accelorometer / Muhammad Faiz Bin Nazri & Muhammad Faiz Bin Musa - Nazri, Muhammad Faiz; Musa, Muhammad Faiz (2015)
These days, many road accident involving motorcyclist often to occur due to their own mistake and careless. The main factor that contribute to this matter is the way their using their left and right signal as well as others safety signal indicator such as brake light. Most of them are often tum out to accidentally give wrong signal and may lead to unwanted situation to themselves and others road user. So, with this project, called "Automatic Motorcycle Signal Indicator Using Arduino UNO and accelerometer'', all the decision to tum on the signal indicator was passed to the Arduino UNO as it's the controller in this project. This project was also featuring the accelerometer, type 3-axis adxl355 as it movement sensor. This project was design using arduino-l.0.5-r2-windows software to deliver a system where the signal indicator can be tum on by only base on the motorcycle movement. By using a simple calculation in the programme , this project can also easily to determine the movement of the motorcycle. Based on the result obtained, the value of X-axis and Y-axis are different in different cases. To put it in a simple note, the higher angle of the left tum ,the bigger the result of the X-axis and vice versa. Meanwhile, the higher the forward angle movement the smaller the Y-axis and vice versa. This project was run perfectly with logical output respond